COMPETENCE-BASED APPROACH IN PROFESSIONAL EDUCATION: PROBLEMS AND PROSPECTS OF IMPLEMENTING INNOVATIVE METHODS USING INFORMATION TECHNOLOGIES - Yunona Sabitovna Mamutova (Bright Mind Publishing, 2025)
This article discusses the problems and prospects of introducing a competence-based approach and innovative methods using information technology in vocational education.
Keywords: Competence, education, technology, innovation, online, digitalization, skills, platform.